Human Verbal Memory Encoding Is Hierarchically Distributed in a Continuous Processing Stream - Kucewicz, Michal T; Saboo, Krishnakant; Berry, Brent M; Kremen, Vaclav; Miller, Laura R; Khadjevand, Fatemeh; Inman, Cory S; Wanda, Paul; Sperling, Michael R; Gorniak, Richard; Davis, Kathryn A; Jobst, Barbara C; et al. (eNeuro, 2019)
Processing of memory is supported by coordinated activity in a network of sensory, association, and motor brain regions. It remains a major challenge to determine where memory is encoded for later retrieval. Here, we used direct intracranial brain recordings from epilepsy patients performing free recall tasks to determine the temporal pattern and anatomical distribution of verbal memory encoding across the entire human cortex. High γ frequency activity (65-115 Hz) showed consistent power responses during encoding of subsequently recalled and forgotten words on a subset of electrodes localized in 16 distinct cortical areas activated in the tasks. More of the high γ power during word encoding, and less power before and after the word presentation, was characteristic of successful recall and observed across multiple brain regions. Latencies of the induced power changes and this subsequent memory effect (SME) between the recalled and forgotten words followed an anatomical sequence from visual to prefrontal cortical areas. Finally, the magnitude of the memory effect was unexpectedly found to be the largest in selected brain regions both at the top and at the bottom of the processing stream. These included the language processing areas of the prefrontal cortex and the early visual areas at the junction of the occipital and temporal lobes. Our results provide evidence for distributed encoding of verbal memory organized along a hierarchical posterior-to-anterior processing stream.
Keywords: gama rytmus EEG; network oscillations; Mental Recall; Humans; mapování mozku; slovní zásoba; cortical mapping; Drug Resistant Epilepsy; Speech Perception; elektrokortikografie; percepce řeči; zraková percepce; lidé; cognition; mozková kůra; Visual Perception; high-frequency oscillations; rozpomínání; časové faktory; Cerebral Cortex; electrocorticography; Brain Mapping; refrakterní epilepsie; Vocabulary; Gamma Rhythm; Electrocorticography; Time Factors